Regulatory factors controlling muscle mass: Competition between innate immune function and anabolic signals in regulation of atrogin-1 in Atlantic salmon. Issue 2 (October 2015) - Heidari, Zeynab; Bickerdike, Ralph; Tinsley, John; Zou, Jun; Wang, Ting-Yu; Chen, Tzong-Yueh; Martin, Samuel A.M.
Highlights: Atrogin-1 is a key protein involved in protein reallocation and protein degradation. Atrogin-1 promoter contains conserved transcription factor binding sites across vertebrates. In fish atrogin-1 promoter responds to proinflammatory cytokines, interferons and insulin like growth factor-1. Abstract: Atrogin-1 is a conserved ubiquitin E3 ligase that is central to the early stages of skeletal and cardiac muscle wasting and degradation following starvation and inflammatory diseases. The control of protein turnover is different between endothermic and ectothermic animals reflecting the body energy requirements. Here we have characterised the promoter of the atrogin-1 gene in a phylogenetically diverse group of vertebrates and show conserved FOXO elements are present in all species examined. We have examined the gene expression responses in primary muscle cell culture to key immune modulators (IL-1β, interferon type 1 and interferon γ) and to the anabolic hormone insulin like growth factor (IGF-1). We show that the IL-1β and interferon type 1 increased atrogin-1 mRNA expression whereas IGF-1 suppressed atrogin-1 expression. The proximal promoter of salmon atrogin-1 was used to transfect primary muscle cell cultures and we found all three cytokines increased promoter activity whereas there was a decrease caused by IGF-1 exposure. We hypothesise that the main drivers for atrogin-1 expression are via the conserved FOXO site, but other transcription binding sites such as NFκB, STAT and IRFs may also be involved in a synergistic manner following immune stimulation when free amino acids need to be released for muscle protein reserves.